PENINGKATAN REGULASI DAN KEBIJAKAN DI INDONESIA UNTUK MENDUKUNG TEKNOLOGI BLOCKCHAIN DALAM PROSES KNOW YOUR CUSTOMER DAN ANTI-MONEY LAUNDERING TERKAIT IMPLEMENTASI PENCEGAHAN PENCUCIAN UANG - Simanjuntak, Efendi; Hafny Afrilies, Marlia; Angel Lina, Angie (LPPM Universitas Harapan Bangsa, 2024)
The digital era has introduced new complexities to the global financial system, where advancements in information technology expand opportunities for criminals to engage in money laundering with increasingly sophisticated and harder-to-trace methods. Money laundering, which harms economic development through various negative impacts such as disruptions to financial stability, reduced state revenue, and damage to national reputation, requires effective preventive measures. This article is the result of research using a juridical-normative method. The findings indicate that the banking system is often used to conceal illegal funds due to its complexity and international nature, facilitating criminals to transfer and convert funds securely and legally. Therefore, blockchain provides a tamper-proof transaction record and allows open access to verify ownership and transactions. This can strengthen anti-money laundering compliance by reducing potential bias, enhancing protection against cyber threats, and ensuring transaction integrity. The adoption of blockchain technology in the financial system can bring paradigm shifts, assisting financial institutions and regulatory bodies in addressing money laundering challenges more effectively and transparently. With its characteristics of transparency and security, blockchain technology offers innovative solutions in Know Your Customer (KYC) and Anti-Money Laundering (AML) processes. Although Bank Indonesia has issued anti-money laundering policies, regulatory and compliance challenges remain in Indonesia. This study uses a normative approach with secondary data from various legal sources to assess the effectiveness of blockchain technology implementation in preventing money laundering.